Larangan Menistakan Agama Dalam Al-Qur’ân Antara Fardu Ain dan Kifayah: Studi Komparatif Atas Tafsir Ibn Katsîr dan Tafsir Al-Mishbâh - Lalu Muhammad Idham Khalid; Abdul Muid N; Muhammad Adlan Nawawi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Today, in times of increasingly complex public problems and the need for religious references has escalated, there is a spirit to answer this with individual and collective da'wah movements. This condition in the opinion of researchers is very good, but often there is a bias in the basic understanding of who is actually entitled and obliged to convey da'wah (who has the right to prohibit blasphemy) and how the law is actually based on the perspective of the Qur'an. The purpose of this study to explore the interpretation of Ibn Katsîr and M. Quraish Shihâb regarding the obligation of Da'wah and the implications of the sociohistorical background of both. The approach used in this study is qualitative with comparative study method. Data collection techniques in the form of literature and observation studies were analyzed in the form of descriptive data collection techniques with the method of comparative analysis (analytical-comparative method). The results showed that there are differences in the tendency of interpretation as well as interpretation between Ibn Katsîr with M. Quraish Shihâb. Ibn Katsîr directed the obligation of Da'wah (which has the right to prohibit blasphemy) as an individual obligation while M. Quraish shihâb directs the tendency of the interpretation of the obligation as a collective obligation also with some similarities in the interpretation of which still accommodate obligations that are not used as a tendency of interpretation